Gender-inclusive consumer studies improve cassava breeding in Nigeria - Madu, T.; Onwuka, S.; Nwafor, S.; Ejechi, M.; Ofoeze, M.; Onyemauwa, N.; Ukeje, B.; Eluagu, C.; Olaosebikan, Olamide; Benjamin Okoye (Frontiers Media, 2024)
Including gender research in cassava breeding makes it easier for farmers to adopt new varieties that meet the specific needs and preferences of both male and female farmers, leading to increased adoption of new varieties, improved productivity, and better economic outcomes for the entire farming community. Gender was included in 2013 in variety development at the National Root Crops Research Institute (NRCRI), Umudike, Nigeria in response to the dis-adoption of some varieties by farmers who had not been part of varietal development from the start, and in light of social roles which influence the responsibilities, resources and livelihood outcomes of men, women and youths. Gender inclusion has given plant breeders accurate information about the cassava traits preferred by all end-users, not just male farmers. At NRCRI, gender studies intensified in the last 5 years, contributing to the development and release of improved varieties. Quantitative and qualitative research by the gender cross-cutting team modeled trait profiling and consumer preferences, to aid demand-led breeding. Some of the methods were acquired at several trainings on how to quantify qualitative responses for prioritization. Gender research techniques include participatory varietal selection (PVS), participatory plant breeding (PPB), mother-baby trials, focus group discussions (FGD), surveys, value chain mapping, G+ tools, experiments in farmer field schools (FFS), demonstration farms, and tricot. These gave the cross-cutting team a better understanding of gender relations, power, decision-making, ownership and control of resources, and have mitigated operational and field challenges during the surveys. These methods also elicited feedback from end-users that led to better naming of newly released varieties, reflecting perceptions of agronomic performance, and food qualities, which made the varieties easier to identify and remember.